Pendampingan Pembangunan Musholla Al-Mujabin dengan Metode Hybrid - Putri, Tika Novis; Syahriyah, Dewi Rachmaniatus; Septian, Ridho; Aulia, Zumrati (Jurnal Pengabdian Tri Bhakti, 2022)
Community Service Activities conduct to assist in the reconstruction of the Al Mujabin mosque which has been badly damaged. Abdimas plays the role of an expert who assists in coordination between the local contractor and representatives of crowdfunding foundations. The purpose of this assistance is to realize the construction of the Al Mujabin Mosque by following the Work Implementation Technical Plan both in terms of design and duration of construction time. To increase funding and time efficiency, the assistance for the construction of the Al Mujabin Mosque was carried out using a hybrid method with one site visit in the middle of the duration of the construction and assistance through Whatsapp, Zoom, and Android-based applications, namely Raken Construction Management. The use of the website and mobile-based technology is effective in assisting coordination between Abdimas, foundations, and field implementers so that the problems and quick solutions needed can be properly accommodated. The output of this community service is the completion of the construction of the Al-Mujabin Mosque in Kertajadi Village, Cidaun District, Cianjur Regency by Architects and Construction Experts following a predetermined design, both in terms of coordination, supervision, problem-solving, and timeliness construction.